PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATA PELAJARAN MATEMATIKA MATERI SATUAN BERAT SISWA KELAS 2 SDN BULUSARI 3 - Widya Murty, Wily Krisna; Putri, Kharisma Eka; Laila, Alfi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the results of a needs assessment questionnaire given to second-grade teachers of SDN Bulusari 3, which showed obstacles in learning the material on weight units and the lack of use of interactive learning media, which has an impact on student learning outcomes that are not optimal. This study aims to determine the validity, practicality, and effectiveness of the development of interactive multimedia on the material on weight units. This study uses the Research and Development (R&D) method with the ADDIE model which includes five stages: Analyze, Design, Development, Implementation, and Evaluation. Data collection techniques include interviews, observations, and questionnaires, and analyzed using a Likert scale. Media validity is obtained from the assessment of material experts and media experts, practicality from teacher and student questionnaires, and effectiveness from posttest results compared with the Minimum Completion Criteria (KKM). The results showed that material validation reached 100% and media validation 91.57%, both of which are included in the very valid category. Media practicality based on teacher responses was 92% and students 97.14% (very practical). The effectiveness of the media showed that 18 students achieved scores above the Minimum Competency (KKM) with a classical passing percentage of 100%. Thus, the developed interactive multimedia proved to be highly valid, practical, and effective, and suitable for use as an interactive learning medium in grade II of elementary school.